Implementasi Sport Science Melalui Pelatihan Badminton Di Desa Rawaapu Tahun 2023 - Ruman Ruman; Kuat Leksono; Farhan Nur Azis (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2023)
Thematic Real Work Lectures (KKN) are KKN whose activity programs focus on certain areas according to social problems and the direction of development policies implemented by certain regional governments. STKIP Darussalam Cilacap organizes a Real Work Lecture program using the thematic method. KKN-T is intended to develop a spirit of empathy and concern for problems that occur in society. The work program created is the Badminton Training Work Program. The main reason is that Rawaapu residents have a great interest in badminton. Therefore, we are moved to hold a badminton training work program so that human resources in Rawaapu can have talented seeds, especially in the world of badminton.